Research on Technical Characteristics and Training Optimization of Starting Technique in Speed Slalom of Freestyle Roller Skating Based on Kinematics and Dynamics - Wei, Jingxiao (Pinnacle Academic Press Proceedings Series, 2026)
This study investigates the starting technique in the speed slalom event of freestyle roller skating from both kinematic and dynamic perspectives, with the aim of providing a scientific basis for performance enhancement. Using a combination of literature review, controlled experiments, and mathematical statistics, the research decomposes the start into distinct phases and systematically examines key spatiotemporal and joint-angle parameters, ground reaction forces, and impulse characteristics. The technical characteristics of elite skaters are summarized in terms of body posture, center-of-mass trajectory, push-off sequence, and force application patterns. On this basis, movement norms, typical parameter ranges, and internal relationships between kinematic variables and dynamic outputs are clarified, highlighting the determinants of rapid acceleration and stability in the initial strides. Guided by these findings, targeted training content and optimization strategies are designed, including specific strength exercises, coordination drills, and start-phase simulation training that emphasize force direction, rate of force development, and technical consistency. The proposed optimization scheme is implemented in practice and its effectiveness is preliminarily verified through comparative performance tests and technical evaluations. The results indicate that structured, biomechanically informed training can significantly improve starting efficiency and technical quality in speed slalom, offering a useful reference for coaches and athletes and contributing to the scientific development and standardization of freestyle roller skating training.